The Struggle of a Geisha in Maintaining Her Pride as Seen in Arthur Golden’s Memoirs of a Geisha - Handriyani, Ramiyati; Astuti, Amelia Yuli (Fakultas Sastra Universitas Ekasakti, 2019)
This thesis is entitled